2004
DOI: 10.1016/s0092-8674(04)00114-x
|View full text |Cite
|
Sign up to set email alerts
|

Complete Polarization of Single Intestinal Epithelial Cells upon Activation of LKB1 by STRAD

Abstract: The LKB1 gene encodes a serine/threonine kinase that is mutated in the Peutz-Jeghers cancer syndrome. LKB1 is homologous to the Par-4 polarity genes in C. elegans and D. melanogaster. We have previously reported the identification and characterization of an LKB1-specific adaptor protein, STRAD, which activates LKB1 and translocates it from nucleus to cytoplasm. We have now constructed intestinal epithelial cell lines in which inducible STRAD activates LKB1. Upon LKB1 activation, single cells rapidly remodel th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

19
431
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 465 publications
(451 citation statements)
references
References 44 publications
19
431
1
Order By: Relevance
“…Several previous studies already demonstrated the requirement of LKB1 and JNK for epithelial integrity and polarity, both in the mammalian and Drosophila systems. 21,22,27,57 Consistently, we observed that inhibition of LKB1 activity during development caused various morphogenesis defects including malformation of adult thoraxes and failure in embryonic dorsal closure. Furthermore, we also showed that LKB1 is required for maintaining adequate JNK activity during embryonic and larval development.…”
Section: Lkb1 Functionally Interacts With Jnksupporting
confidence: 64%
See 1 more Smart Citation
“…Several previous studies already demonstrated the requirement of LKB1 and JNK for epithelial integrity and polarity, both in the mammalian and Drosophila systems. 21,22,27,57 Consistently, we observed that inhibition of LKB1 activity during development caused various morphogenesis defects including malformation of adult thoraxes and failure in embryonic dorsal closure. Furthermore, we also showed that LKB1 is required for maintaining adequate JNK activity during embryonic and larval development.…”
Section: Lkb1 Functionally Interacts With Jnksupporting
confidence: 64%
“…19,20 Finally, LKB1 was shown to be necessary for the polarization of intestinal epithelial cells and Drosophila ovary cells, demonstrating another important function of LKB1 in regulating cell structure. 21,22 Although considerable progress has been made to characterize the in vivo function of LKB1, only a limited amount of information concerning its molecular mechanisms has been found in detail; the major biological pathway responsible for the tumor suppressive function of LKB1 remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…These observations indicate that LKB1 is a tumor suppressor acting upstream of PAR1. Indeed, LKB1 is a mammalian ortholog of C. elegans PAR4 and is involved in polarity regulation in mammalian cells (Baas et al, 2004). The causal link between LKB1 and the cancer-prone PeutzJeghers syndrome supports the idea that defects in epithelial polarity are required for the development of epithelial tumors.…”
Section: Function Of Par1 In Carcinogenesismentioning
confidence: 79%
“…(1) remodeling of the actin cytoskeleton to an apical brush border, (2) relocalization of zona occludens 1 and p120-catenin to form junctional complexes and (3) the sorting of surface proteins to apical and basolateral domains (Baas et al, 2004a). LKB1 can also regulate the polarization of lung cancer cell lines in association with recruitment of the small GTPase, Cdc42, a known regulator of cell polarity see Etienne-Manneville, 2008).…”
Section: Polarity Controlmentioning
confidence: 99%
“…Kinase-dead mutants of LKB1 are incapable of inducing polarity in Drosophila and in mammalian intestinal epithelial cells indicating that LKB1 catalytic function is required (Forcet et al, 2005). In addition, mammalian cells require STRAD-mediated translocation of LKB1 from the nucleus to the cytoplasm (Baas et al, 2004a). Beyond these general features, it is likely the LKB1 controls cell polarity in a cell type-specific manner with different contributions from individual AMPK family members.…”
Section: Mechanisms Of Polarity Controlmentioning
confidence: 99%